2018
DOI: 10.1111/tpj.13826
|View full text |Cite
|
Sign up to set email alerts
|

Defective XRN3‐mediated transcription termination in Arabidopsis affects the expression of protein‐coding genes

Abstract: Arabidopsis thaliana contains two nuclear XRN2/3 5'-3' exonucleases that are homologs of yeast and human Rat1/Xrn2 proteins involved in the processing and degradation of several classes of nuclear RNAs and in transcription termination of RNA polymerase II. Using strand-specific short read sequencing we show that knockdown of XRN3 leads to an altered expression of hundreds of genes and the accumulation of uncapped and polyadenylated read-through transcripts generated by inefficiently terminated Pol II. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 62 publications
(91 reference statements)
6
48
1
Order By: Relevance
“…These pathways may involve the nuclear 5'-3' exonucleases XRN2 and XRN3. XRN2 has documented functions in ribosomal RNA cleavage (Zakrzewska-Placzek et al, 2010) , while XRN3 has more identified nuclear substrates, including RNA polymerase II-associated RNA and cleavage products by DICER-LIKE enzymes, the former giving rise to defects in transcription termination in xrn3 mutants (Krzyszton et al, 2018) . In addition, the heptameric nuclear Lsm complex, Lsm2-8, a well-established pre-mRNA splicing factor (Bouveret et al, 2000;Tharun et al, 2000) , also plays roles in nuclear RNA decapping and, ultimately, decay, presumably via 5'-3' exonucleolysis (Golisz et al, 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…These pathways may involve the nuclear 5'-3' exonucleases XRN2 and XRN3. XRN2 has documented functions in ribosomal RNA cleavage (Zakrzewska-Placzek et al, 2010) , while XRN3 has more identified nuclear substrates, including RNA polymerase II-associated RNA and cleavage products by DICER-LIKE enzymes, the former giving rise to defects in transcription termination in xrn3 mutants (Krzyszton et al, 2018) . In addition, the heptameric nuclear Lsm complex, Lsm2-8, a well-established pre-mRNA splicing factor (Bouveret et al, 2000;Tharun et al, 2000) , also plays roles in nuclear RNA decapping and, ultimately, decay, presumably via 5'-3' exonucleolysis (Golisz et al, 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…Detection in nuclear exosome mutants and nascent transcript preparation gives asCBF1 characteristics of a cryptic lncRNA that is quickly cleaved and degraded in wild-type. The XRN3 is thought to represent the 5'-to-3' torpedo exonuclease mediating transcriptional termination in Arabidopsis 30,31 . However, we did not observe the asCBF1 RNA or CBF1 mis-regulation in the xrn3-3 mutant, suggesting that this effect is XRN3 independent (Supplementary Fig.…”
mentioning
confidence: 99%
“…Nascent transcript cleavage creates the 3'-end of the full length mRNA substrate for poly-adenylation, and a free 5'-end is attacked by 5' to 3' exonucleases eliciting transcription termination according to the torpedo model 29,30 . To detect any read-through transcription from SVK, we purified nascent RNA associating with RNAPII complexes (Supplementary Fig.…”
mentioning
confidence: 99%
“…Inhibition of XRNs by PAP (Dichtl et al, 1997), leads to the activation of 25 % of the high light stress transcriptome, including genes encoding antioxidant enzymes such as Ascorbate Peroxidase 2 (APX2) (Estavillo et al, 2011). Recent work by Crisp et al (2018) and Krzyszton et al (2018) provided valuable insights into the paradox of how specificity in the regulation of nuclear gene expression by PAP is achieved, given that the XRNs are not transcription factors which bind to specific DNA motifs. PAP-mediated inhibition of XRNs leads to inefficient removal of Pol II upon completion of transcription a particular gene, thereby facilitating polymerase read-through to the downstream gene and increasing transcription of this downstream gene.…”
Section: Degradation Intracellular Transport and Nuclear Function Omentioning
confidence: 99%